Development through positive deviance and its implications for economic policy making and public administration in Africa: The case of agricultural development in Kenya, 1930 -2005 - Ochieng, Cosmas M. O. (Elsevier, 2007)
Positive internal innovation has long been a central element of African agricultural development, even if modern efforts to stimulate technical, institutional, and policy innovations in African agriculture have tended to look outwards. This paper examines the role of positive deviance in Kenyan agriculture over the last 75 years to cast doubt on the alleged authoritative sources of policy advice and mandates from the outside. Positive deviance and appreciative inquiry are suggested as organizing frameworks for identifying and amplifying the generation and uptake of internal African innovations.